2010
DOI: 10.1177/104063871002200415
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of Porcine Teschovirus from Nervous Tissue of Pigs with and without Polioencephalomyelitis in Indiana

Abstract: Abstract. Porcine teschovirus (PTV) was isolated in cell culture and/or demonstrated by polymerase chain reaction in samples of brain and/or spinal cord in pigs in Indiana during the 2002-2007 period. Testing was initiated on pigs originating from populations exhibiting nervous clinical disease and/or pigs with microscopic lesions in central nervous tissues, indicating viral encephalitis and/or myelitis. Virus was demonstrated in pigs with and without lesions as well as with and without nervous clinical diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…In addition to enteroviruses, sapeloviruses and teschoviruses, many picornaviruses have been detected in pigs: Foot-and-mouth disease viruses, encephalomyocarditis viruses, porcine cosaviruses, kobuviruses, pasiviruses, senecaviruses and tottoriviruses. The genus Teschovirus has been frequently associated with neurologic disease in pigs [2][3][4][5]. Porcine teschovirus (PTV) currently comprises 13 known serotypes [6][7][8], which is likely to expand with the continuous discovery of novel genotypes [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to enteroviruses, sapeloviruses and teschoviruses, many picornaviruses have been detected in pigs: Foot-and-mouth disease viruses, encephalomyocarditis viruses, porcine cosaviruses, kobuviruses, pasiviruses, senecaviruses and tottoriviruses. The genus Teschovirus has been frequently associated with neurologic disease in pigs [2][3][4][5]. Porcine teschovirus (PTV) currently comprises 13 known serotypes [6][7][8], which is likely to expand with the continuous discovery of novel genotypes [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the disease spreads throughout Europe and other continents during the 1940s and 1950s, causing devastating economic losses. At present, a mild form of the disease, with the exception of an outbreak in 2009 in the Republic of Haiti, has been described in many countries (Bangari, Pogranichniy, Gillespie, & Stevenson, ; Deng et al., ; Knowles, ; Pinto, Ankers, Werthmann, & Hamilton, ; Salles et al., ; Takahashi, Seimiya, Seki, & Yamada, ; Wang et al., ; Yamada et al., ; Zhang et al., ). The first documented PTV isolate (Swine/CH/IMH/03) in China was identified in 2003, and some cases and epidemiological studies related to PTV in China have been reported since then (Feng et al., ; Lin et al., ; Qiu, Wang, Zhang, Zhang, & Cui, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, depending on the virus serotype and infection conditions, these picornaviruses may be considered important etiological agents of enteric, respiratory, reproductive, or neurological disorders (Bangari et al 2010, Ventura et al 2013. Clinical manifestations may include diarrhea, pneumonia, febrile illness, vesicular diseases, reproductive failure (SMEDI syndrome), myocarditis, and polioencephalomyelitis (Krumbholz et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Studies performed in different geographical regions throughout the world revealed that PTV, PSV, and EV-G are ubiquitous and have been reported in Asia (Kaku et al 2007, Lan et al 2011, Lin et al 2012, Moon et al 2012, Zhang et al 2012, Europe (Zell et al 2000, La Rosa et al 2006, Buitrago et al 2010, Sozzi et al 2010, Boros et al 2011, ProdÄ›lalová 2012, and the Americas (Bangari et al 2010, Salles et al 2011, Shan et al 2011, Deng et al 2012, Ventura et al 2013, Donin et al 2014.…”
Section: Introductionmentioning
confidence: 99%